(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2006)
The Shemshak Formation is well-exposed in Narges-Chal area, East Alborz. It contains abundant well-preserved plant megafossils belonging to twenty two taxa of various orders viz., Equisetales, Marattiales, Filicales, Pteridospermales, Bennettitales, Ginkgoales, and Coniferales. Based on the occurrence of Equisetites conicus, Scytophyllum persicum, Otozamites ashtarensis, Pterophyllum bavieri, Pterophyllum tietzei, Zamites persica, Nilssoniopteris musafolia and Baiera muensteriana a Rhaetian age is suggested for this assemblage.